Platelet ascorbic acid levels in normal subjects and in disease. Issue 6 (June 1972) - Lloyd, J. V.; Davis, P. S.; Emery, H.; Lander, H.
Abstract : The platelet ascorbic acid concentration was measured in 26 normal subjects and found to be 20 times as high as in plasma. This is in agreement with previous reports in the literature. The platelets of patients with uraemia, leukaemia, and megaloblastic anaemia had a lower than normal platelet ascorbic acid content. In uraemia and megaloblastic anaemia the plasma ascorbic acid concentration was normal suggesting that a platelet defect may be responsible for the low platelet ascorbic acid content. In leukaemia the low platelet ascorbic acid content is probably secondary to a low plasma level.